The effect of dual stimulation on ploidy rates in patients with poor ovarian response - Aygün, Elif Ganime; Karabuk, Emine (Journal of Surgery and Medicine, 2021)
Background/Aim: It is difficult to obtain healthy oocytes in poor ovarian response patients with conventional treatment methods. This study aimed to find out which agent is most effective at inducing ovulation in one menstrual cyle. We aimed to examine the effects of follicular and luteal stimulation in patients with poor ovarian response on oocyte count, blastocyst, euploid embryo, and pregnancy rates. Methods: A total of 134 patients were included in this retrospective cohort study, and the rates of ploidy in the embryos obtained by follicular and luteal stimulation were evaluated. All cases were treated with the antagonist protocol beforehand. The research was conducted by examining the data of patients who underwent Dual stimulation (Duostim) between 2015 and 2017 in the IVF Clinic of Acıbadem University Atakent Hospital retrospectively. Results: While ploidy rates in FS and LS were significant in terms of age and AMH values (P<0.05 for all), they did not differ with BMI values (P>0.05 for all). The rate of aneuploid embryo development in follicular phase was 81.8%, while that in luteal phase was 18.2%, and the rates of euploid embryo development in follicular and luteal treatments were 34.6% and 18.2%, respectively. The pregnancy rate with euploid embryos by LPS was significantly higher compared that by FPS (P<0.05). Conclusion: Our study concludes that follicles entering the anovulatory phase in the follicular phase can be saved by LS, so that healthier embryos can be obtained.